Enhanced fluorescence from x-ray line coincidence pumping of K-pumped Cl and Mg-pumped Ge plasmas - Nilsen, J; Burridge, D; Hobbs, LMR; Hoarty, D; Beiersdorfer, P; Brown, GV; Hell, N; Panchenko, D; Gu, MF; Saunders, AM; Scott, HA; London, RA; et al. (Society of Photo-optical Instrumentation Engineers, 2019)
Many resonant photo-pumped X-ray laser schemes that use a strong pump line such as Ly-α or He-α to populate the upper laser state of a separate lasing material have been proposed over the last four decades but none have been demonstrated. As a first step to creating a photo-pumped X-ray laser we decided to reinvestigate some of these schemes at the Orion laser facility with the goal to demonstrate enhanced fluorescence as a first step toward creating a laser. In particular we look at using the Ly-α or He-α K lines to pump the 1s – 3p and 4p transitions in H-like Cl and see fluorescence on the 4f -3d line at 65 Å and the 3d – 2p line at 23 Å. Preliminary experiments are presented that show a modest enhancement of 40% on the 3d-2p line. As an alternative we also look at enhancing the 2p – 2s line in Ne-like Ge at 65Å using the Ly-α Mg line to photo-pump the 2s – 3p line of Ne-like Ge. Calculations are presented that suggest modest enhancements of 2.5 and recent experiments will be presented that show emission from a Ge plasma pumped by the Ly-α Mg line.